Identifying university opinion leaders during the global crisis: information communication on official websites - Xin Guo; Zhuolin Feng (Humanities & Social Sciences Communications)
Abstract This study investigates the news articles about the global crisis published by university official websites, aiming to identify opinion leaders from world-class universities. Based on the characteristics of opinion leaders, content analysis is used to analyze the case of COVID-19. The professionalism of all information is assessed through qualitative analysis, and activity and centrality are quantified by descriptive statistics and social network analysis, respectively. The findings of this study indicate that these three criteria can be used to assess universities. University opinion leaders show the characteristics of high professionalism, high activity and high centrality. Influenced by the institutional traits of world-class universities, university opinion leaders are divided into different types. Playing a comprehensive and multidimensional role may enable the public to quickly recognize their contributions through multiple channels, thereby gaining wide recognition. Moreover, extensive information sharing facilitates effective coordination of crisis management activities with global institutions. Some iconic brand achievements enhance their overall influence, producing a halo effect. This study is one of the first exploratory attempts to identify university opinion leaders, integrating communication theory with practical application in higher education.